Impact of Vocabulary Learning Strategies on Gender Based ESL Learners in Pakistan - Bhatti, Muhammad Safdar; Mukhtar, Rafia (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The wide spectrum of English language compels readers to find out the exact crux of the language itself. English has won the status of international language. It has become a dire need of this age. The English language is comparatively difficult due to its pronunciation, sentence structure and vocabulary level from local languages in Pakistan. Vocabulary is the utmost aspect of learning a second language. It is the essence and soul of language. The language process depends on learning vocabulary. So the current paper investigates the impact of vocabulary learning strategies for the ESL learners in Pakistan. It was an experimental type of research. One hundred students of Grade-9 in the academic year 2019-20 participated in this study. The data was collected through test and questionnaire. The study results revealed that the students who were taught by the ESL learning techniques (semantic mapping, imaging and pics, visual and auditory, group association and word contact) performed better as compared with the students in the traditional vocabulary learning method. Female students performed better in the experimental group. ESL male learners used group association learning technique at priority, and ESL female learners used visual and auditory learning at their priority. The researchers recommend that English language teachers should use vocabulary learning strategies for teaching English to ESL learners.